2020
DOI: 10.3892/ijo.2020.5077
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of combined treatment with mild hypothermia and edaravone against cerebral ischemia/reperfusion injury via oxidative stress and Nrf2 pathway regulation

Abstract: Mild hypothermia (MH) and edaravone (EDA) exert neuroprotective effects against cerebral ischemia/reperfusion (I/R) injury through activation of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway. However, whether MH and EDA exert synergistic effects against cerebral I/R injury remains unknown. The aim of the present study was to investigate the effects and mechanism of action of MH in combination with EDA in cerebral I/R injury. A rat cerebral I/R injury model was constructed by middle cerebral ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The levels of malondialdehyde (MDA) (S0131), antioxidant enzyme superoxide dismutase (SOD) (S0101), and glutathione (GSH)/oxidized glutathione (GSSG) (S0053) were measured using ELISA assay kits according to the manufacturer’s instructions (Beyotime Biotechnology, Shanghai, China). Briefly, MDA detection was based on the chromogenic reaction between MDA and thiobarbituric acid, and measured at 535 nm light wave [ 33 ]. SOD analysis was performed according to the WST-8 method and detected at 450 nm light wave [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of malondialdehyde (MDA) (S0131), antioxidant enzyme superoxide dismutase (SOD) (S0101), and glutathione (GSH)/oxidized glutathione (GSSG) (S0053) were measured using ELISA assay kits according to the manufacturer’s instructions (Beyotime Biotechnology, Shanghai, China). Briefly, MDA detection was based on the chromogenic reaction between MDA and thiobarbituric acid, and measured at 535 nm light wave [ 33 ]. SOD analysis was performed according to the WST-8 method and detected at 450 nm light wave [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…SOD analysis was performed according to the WST-8 method and detected at 450 nm light wave [ 34 , 35 ]. The GSH/GSSG assay was performed by glutathione reductase treatment and the concentration is detected at 412 nm light wave [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was used to measure protein levels in cortical or cellular samples as discussed previously ( 24 ). Briefly, samples were lysed in RIPA buffer and centrifuged at 13,362 g for 15 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of genes involved in the Nrf2 pathway was upregulated following edaravone treatment in TDP-43-expressing 1464R cells in the presence of ethacrynic acid. It was previously shown that edaravone activates the Nrf2/HO-1 pathway, exerts neuroprotective effects (including a reduction of neurological and cognitive dysfunction), and protects against cell apoptosis in mouse and rat models of various neurological disorders [ 39 , 40 , 41 , 42 ]. In the Nrf2/G93A mouse model of ALS pathology, the expression of Nrf2 was accelerated in both spinal cord motor neurons and lower limb muscles during disease progression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%